2014
DOI: 10.1007/s12094-014-1223-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of circulating endothelial cells as a predictor of response to chemotherapy with platinum and pemetrexed in patients with advanced non-squamous non-small cell lung carcinoma

Abstract: In this homogeneous group of patients with NSCLC, there is no correlation between response to treatment and CEC baseline levels. The increase in CEC numbers after the first cycle could be a negative predictive factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…According to the 75 th percentile of CEC counts for the entire group, we found that baseline CEC count was not a predictive factor for either PFS or OS in advanced NSCLC patients. Our results were consistent with the findings of previous studies, in which more recent techniques have been used for CEC enumeration (35, 36). Using flow cytometry, no significant difference in the median PFS duration was obtained between NSCLC patients with high basal CEC levels and those with low CEC levels at diagnosis (35).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…According to the 75 th percentile of CEC counts for the entire group, we found that baseline CEC count was not a predictive factor for either PFS or OS in advanced NSCLC patients. Our results were consistent with the findings of previous studies, in which more recent techniques have been used for CEC enumeration (35, 36). Using flow cytometry, no significant difference in the median PFS duration was obtained between NSCLC patients with high basal CEC levels and those with low CEC levels at diagnosis (35).…”
Section: Discussionsupporting
confidence: 93%
“…Using flow cytometry, no significant difference in the median PFS duration was obtained between NSCLC patients with high basal CEC levels and those with low CEC levels at diagnosis (35). Similar results were recorded for both PFS and OS in advanced nonsquamous subtypes according to the mean level of CECs quantified using the semiautomated IMS technique (36). However, no significant difference in baseline CEC levels was observed among histological subtypes in NSCLC (33, 37).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…It was therefore the aim of the present study to investigate the prognostic value of CEC in patients with CRC liver metastases who underwent potentially curative therapy using the semi-automated and highly reproducible CellSearch System for CEC detection [8,1012]. As CTC are well-established prognostic markers in primary and metastatic CRC [1322], we aimed to evaluate the prognostic value of CEC in a ‘head-to-head’ comparison with CTC in the same cohort of patients with metastatic CRC.…”
Section: Introductionmentioning
confidence: 99%